Implementation of Importance-Performance Analysis on Integrated Information System Institut Teknologi Telkom Purwokerto - Dina Rachmawaty; Achmad Zaki Yamani; Famila Dwi Winati; Hawwin Mardhiana (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
Improving information systems is essential to increase user satisfaction which then has a positive impact on the institution. This study aims to measure the importance and performance of website service quality attributes on the i-Gracias ITTP using Importance Performance Analysis. This study integrate e-ServQual and WebQual to measure the level of student satisfaction with i-Gracias as a web-based information system service comprehensively. Generally, the satisfaction score shows that the performance of quality attributes does not meet the expectations of students as users. Of the 30 quality attributes measured, there is one attribute in quadrant I, 12 in quadrant II, 13 in quadrant III, and 3 in quadrant IV. The attributes that describe the fundamental functions of i-Gracias as an online service system are efficiency, security, fulfillment, information quality, and accessibility. The next priority for improvement for i-Gracias is efficiency improvement and process simplification.